2022
DOI: 10.1111/dom.14855
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome coronavirus 2 spike antibody level decline is more pronounced after the second vaccination, but response to the third vaccination is similar in people with type 1 and type 2 diabetes compared with healthy controls: The prospective COVAC‐DM cohort study

Abstract: Up to 1 June 2022, almost 12 billion vaccine doses for coronavirus disease 2019 (COVID-19) were administered worldwide. 1 People with diabetes were more probable to be hospitalized for COVID-19 and were observed to have in-hospital mortality as high as 25%. 2,3 Hence COVID-19 vaccination is not only recommended with priority in people with diabetes, it has also been shown to be effective in people with diabetes. 4,5 Our research group previously showed that humoral immune response 2-3 weeks after the second CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Meanwhile, Cheng et al revealed decreased titers of anti‐N/S IgG and anti‐RBD IgG in patients with T2DM compared to HCs 22 . In addition, numerous studies also indicated reduced immunogenicity to mRNA or viral vector‐based COVID‐19 vaccines after finishing full‐course immunization 4,5,13 . Therefore, it is necessary for patients with T2DM to acquire a booster vaccination to improve the effectiveness of the vaccine 14 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Meanwhile, Cheng et al revealed decreased titers of anti‐N/S IgG and anti‐RBD IgG in patients with T2DM compared to HCs 22 . In addition, numerous studies also indicated reduced immunogenicity to mRNA or viral vector‐based COVID‐19 vaccines after finishing full‐course immunization 4,5,13 . Therefore, it is necessary for patients with T2DM to acquire a booster vaccination to improve the effectiveness of the vaccine 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary for patients with T2DM to acquire a booster vaccination to improve the effectiveness of the vaccine 14 . Sourij et al demonstrated a higher antibody response in patients with T2DM inoculated with the third dose of COVID‐19 mRNA vaccine than with the second dose, and response to the third vaccination showed no significant difference between patients with T2DM and HCs 5 . In this study, we also observed enhanced humoral reactivity in patients with T2DM after the booster dose of inactivated vaccine compared to those after receiving the second dose of vaccine, including anti‐SARS‐CoV‐2 total antibodies ( p = 0.002; Figure S1A), anti‐RBD IgG ( p = 0.0025; Figure S1B), and NAb toward WT ( p = 0.0056; Figure S1C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations